Gambaran Klinikopatologi Limfoma Sel B Besar Difus Tidak Tertentu di Rumah Sakit Umum Pusat Dr. Hasan Sadikin Bandung Tahun 2018-2023 - Afiati; Hernowo, Bethy S.; Aminah, Hermin; Oehadian, Amaylia (Majalah Patologi Indonesia, 2025)
Introduction Diffuse large B-cell lymphoma, not otherwise specified (DLBCL, NOS), is the most common group of non-Hodgkin malignant lymphoma globally, representing 25%-40% of adult lymphoma cases. According to the cell of origin(COO), DLBCL NOS is classified into DLBCL germinal center B-cell like(GCB) and DLBCL non-germinal center B-cell like(non-GCB). Since the COO affects the prognosis of DLBCL NOS, this examination is important. Hans algorithm is the most frequently used to distinguish the GCB from non-GCB. This study aims to describe clinicopathological characteristics of DLBCL NOS at Dr. Hasan Sadikin General Hospital Bandung, 2018-2023. Methods The subjects of this retrospective descriptive study were DLBCL GCB and non-GCB patients based on Hans algorithm by IHC examination of CD10, BCL6, and MUM1 who received R-CHOP therapy at Dr. Hasan Sadikin General Hospital from 2018 to 2023. All data contained age, gender, B-symptoms, primary tumor location, stage, total International Prognostic Index (IPI) score, and immunochemotherapy status.  Results A total of 55 patients diagnosed with DLBCL NOS were collected in this study. 50 patients(90.9%) were classified as DLBCL non-GCB and 5 patients(9.1%) were classified as DLBCL GCB. The average age was 62 years, predominantly males(52.7%), extranodal disease(54.5%), no B symptoms(76.4%), and early stage(83.7%). 52 patients(94.6%) had a total IPI score of 0-1, 3 patients(5.4%) had a total IPI score of 2. 21 patients(38.2%) had a response, 13 patients(23.6%) had non-response, and 21 patients(38.2%) are still ongoing to R-CHOP therapy. Conclusion DLBCL NOS at Dr. Hasan Sadikin General Hospital from 2018-2023 mainly occurred in men with an average 62 years old and extranodal disease without B-symptoms. DLBCL non-GCB was predominant than GCB. Both DLBCL Non-GCB and GCB were mostly diagnosed at early stage, IPI low-risk group, and had response status to R-CHOP therapy similar to those are still ongoing to R-CHOP therapy.